Risk variants in BMP4 promoters for nonsyndromic cleft lip/palate in a Chilean population - Suazo José; Tapia Julio C; Santos José Luis; Castro Víctor G; Colombo Alicia; Blanco Rafael (BMC, 2011)
Abstract Background Bone morphogenetic protein 4 gene (BMP4) plays a key role during maxillofacial development, since orofacial clefts are observed in animals when this gene is conditionally inactivated. We recently reported the existence of association between nonsyndromic cleft lip/palate (NSCLP) and BMP4 polymorphisms by detecting transmission deviations for haplotypes that include a region containing a BMP4 promoter in case-parent trios. The aim of the present study was to search for possible causal mutations within BMP4 promoters (BMP4.1 and BMP4.2). Methods We analyzed the sequence of BMP4.1 and BMP4.2 in 167 Chilean NSCLP cases and 336 controls. Results We detected three novel variants in BMP4.1 (c.-5514G > A, c.-5365C > T and c.-5049C > T) which could be considered as cleft risk factors due to their absence in controls. Additionally, rs2855530 G allele (BMP4.2) carriers showed an increased risk for NSCLP restricted to males (OR = 1.52; 95% C.I. = 1.07-2.15; p = 0.019). For this same SNP the dominant genotype model showed a higher frequency of G/G+G/C and a lower frequency of C/C in cases than controls in the total sample (p = 0.03) and in the male sample (p = 0.003). Bioinformatic prediction analysis showed that all the risk variants detected in this study could create new transcription factor binding motifs. Conclusions The sex-dependent association between rs2855530 and NSCLP could indirectly be related to the differential gene expression observed between sexes in animal models. We concluded that risk variants detected herein could potentially alter BMP4 promoter activity in NSCLP. Further functional and developmental studies are necessary to support this hypothesis.